Location theory and decision analysis analytics of spatial information technology - Chan, Yupo; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Employing state-of-the art quantitative models and case studies, Location Theory and Decision Analysis provides the methodologies behind the siting of such facilities as transportation terminals, warehouses, housing, landfills, state parks and industrial plants. Through its extensive methodological review, the book serves as a primer for more advanced texts on spatial analysis, including the monograph on Location, Transport and Land-Use by the same author. Given the rapid changes over the last decade, the Second Edition includes new analytic contributions as well as software survey of analytics and spatial information technology.  While the First Edition served the professional community well, the Second Edition has substantially expanded its emphasis for classroom use of the volume. Extensive pedagogic materials have been added, going from the fundamental principles to open-ended exercises, including solutions to selected problems. The text is of value to engineering and business programs that offer courses in Decision and Risk Analysis, Muticriteria Decision-Making, and Facility Location and Layout. It should also be of interest to public policy programs that use geographic Information Systems and satellite imagery to support their analyses.
Electronic reproduction.
Keywords: Electronic book; Industrial location -- Decision making; Land use, Urban -- Decision making; Transportation -- Planning; Land use -- Planning; Space in economics -- Mathematical models; Regional economics -- Mathematical models